METODE KALIBRASI TIME DIFFERENT OF ARRIVAL TDOA UNTUK SISTEM PASSIVE RADAR TRAYEKTORI ROKET - Widada, Wahyu; Kliwati, Sri (BRIN Publishing, 2007)
Design passive ranging base on radio with Time Different of Arrival TDOA (passive RADAR) have been developed for the application of tracking rocket trajectory. Calibration of the passive RADAR can be done in launching site for obtaining optimal position, however it is also require to be done in laboratory for testing the system algorithm. This article describes the calibration method of time delay calculation in laboratory using antenna cable with various of lengths. We obtain an accurate correlation results between time delay from measurement of oscilloscope and calculation TDOA with cross-correlation method. This method is practical and effective for calibration system in the development of passive RADAR. Keywords: TDOA, Passive RADAR, Trajectory rocket, Calibration method, Cross-correlation.-